2020
DOI: 10.1111/bju.15068
|View full text |Cite
|
Sign up to set email alerts
|

Improving management of upper tract urothelial carcinoma

Abstract: In other medical fields, it is significant that the value of diagnostic tests is not questioned. For instance, no orthopaedic surgeon would operate on a femoral fracture without access to a good quality X-ray showing the whole femur. In urological oncology, removal of the bladder or kidney would never be contemplated without an understanding of the full clinical picture based on objective diagnostic measures. In short, reliable diagnosis is essential for appropriate decision-making, especially considering the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 7 publications
1
6
0
Order By: Relevance
“…Whilst some centres adopt this policy for all patients to reduce the negative ‘non‐urothelial’ RNU specimen (quoted at 7% in the One Dose Mitomycin C [ODMIT‐C] trial [2], and 10.6% in 2012 BAUS Audit of RNU Practice [3]), there are downsides with an extra invasive procedure, potential delays to definitive treatment and increased risk of intravesical recurrence. In this series, 43% did not undergo ureteroscopy prior to RNU (which is similar to our practice at 46% [4]). This study has confirmed previous reports and meta‐analyses of a higher risk of intravesical recurrence after ureteroscopy [5].…”
supporting
confidence: 61%
See 2 more Smart Citations
“…Whilst some centres adopt this policy for all patients to reduce the negative ‘non‐urothelial’ RNU specimen (quoted at 7% in the One Dose Mitomycin C [ODMIT‐C] trial [2], and 10.6% in 2012 BAUS Audit of RNU Practice [3]), there are downsides with an extra invasive procedure, potential delays to definitive treatment and increased risk of intravesical recurrence. In this series, 43% did not undergo ureteroscopy prior to RNU (which is similar to our practice at 46% [4]). This study has confirmed previous reports and meta‐analyses of a higher risk of intravesical recurrence after ureteroscopy [5].…”
supporting
confidence: 61%
“…In an attempt to reduce ‘unnecessary ureteroscopy’, we have previously reported our outcomes in streamlining this decision making via a dedicated UTUC meeting within the context of the wider specialist bladder cancer multi‐disciplinary team (MDT) meeting [4]. With this approach, we have demonstrated a reduction in both the number of diagnostic ureteroscopies prior to RNU and the average time from referral to definitive surgery, all with no detriment to oncological outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, these results shed a new light on local staging of UTUC, and, once replicated in larger studies, they could support a relevant change in diagnostic workup and treatment planning of UTUC. In fact, biopsy and urinary cytology, which are included in risk stratification, are often not diagnostic [21]. A precise MRI description of the muscle layer infiltration could be added to the factors distinguishing high-from low-risk patients, in addition to the generic and insufficient definition of "local invasion on CT" as defined in the European Association of Urology guidelines [7].…”
Section: Discussionmentioning
confidence: 99%
“…Urothelial carcinoma (UC) is the most common malignancy of the urinary tract. However, upper tract (renal pelvis and ureter) tumors account for only 5% to 10% of all UCs, and almost 60% of upper tract UCs (UTUCs) are invasive at diagnosis (1,2). Currently available prognostic tools that utilize clinical and pathological parameters are limited for UTUC.…”
Section: Introductionmentioning
confidence: 99%